A New Variable Exponential Power Reaching Law of Complementary Terminal Sliding Mode Control - Feng Xu; Na An; Jianlin Mao; Shubo Yang (Complexity)
In this article, a new nonlinear algorithm based on the sliding mode control is developed for the ball and plate control system to improve dynamic response and steady-state tracking accuracy of the control system. First, a new sliding mode reaching law is proposed, variable exponential power reaching law (VEPRL), which is expressed in two different forms including a nonlinear combination function term and a variable exponential power term, so that it can be adjusted adaptively according to the state of the system by the variable exponential power reaching term during the reaching process. The computation results show that it can not only effectively weaken the chattering phenomenon but also increase the rate of the system state reaching to the sliding mode surface. Moreover, it has the characteristic of global finite-time convergence. Besides, a complementary terminal sliding mode control (CTSMC) method is designed by combining the integral terminal sliding surface with the complementary sliding surface to improve the convergence rate. Based on the proposed VEPRL and CTSMC, a new sliding mode control method for the ball and plate system is presented. Finally, simulation results show the superiority and effectiveness of the proposed control method.